Rick and Morty. Season 2 [videorecording (DVD)] - Roiland, Justin, 1980-; Harmon, Dan, 1973- (Warner Home Video, 2016)
Rick Sanchez is still living with his daughter Beth's family and causing more trouble than ever. This season the rest of the family, his son-in-law Jerry, grand-daughter Summer and grand-son Morty are dragged into Rick's intergalactic adventures, as he faces new threats and mysteries of his secret past are revealed. Can the family survive Rick's insanity and all the chaos the universe throws at them?